2016
DOI: 10.1097/nor.0000000000000226
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Nurses' Pain Assessment to Improve Patient Satisfaction

Abstract: Patient satisfaction with pain management has increasing importance with Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) scores tied to reimbursement. Previous studies indicate patient satisfaction is influenced by staff interactions. This single-group pre/post design study aimed to improve satisfaction with pain management in older adults undergoing total joint replacement. This was a single-group pre-/posttest design. Nurse (knowledge assessment) and patient (American Pain Society P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
(33 reference statements)
1
24
0
1
Order By: Relevance
“…Finally, two studies did not report p values. One involved the development and deployment of a Pain Management education module for nurses on an orthopaedic unit, showing potential improvement in Pain Management,18 while the other was a personalised pharmacist intervention for transition of care, with potential improvement in Communication about Medicine 21. Both studies used HCAHPS scores for pre-post assessment but did not report sample sizes or statistical testing for HCAHPS comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, two studies did not report p values. One involved the development and deployment of a Pain Management education module for nurses on an orthopaedic unit, showing potential improvement in Pain Management,18 while the other was a personalised pharmacist intervention for transition of care, with potential improvement in Communication about Medicine 21. Both studies used HCAHPS scores for pre-post assessment but did not report sample sizes or statistical testing for HCAHPS comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Pain management is complex and multifactorial, and hence, a deeper understanding of the barriers to proper and optimum pain management needs to be gained to remedy deficiencies among professionals and to improve patient care. [182627] In the present study, the majority of nurses (77.1%) reported that they had not heard about pain as a fifth vital sign before. In addition, most of the nurses were assessing pain only once a day per patient in line with the quality policy of the institution, and some were not assessing it at all.…”
Section: Discussionmentioning
confidence: 53%
“…Second, the structural variation of tools in terms of items, scales and subscales makes it difficult to aggregate results from across studies that have used the same tool and to compare practice across contexts. This is further hampered by the fact that some studies did not use a tool in its entirety, instead administering individual items (Field, ; Pajnkihar, Stiglic, & Vrbnjak, ; Schroeder et al, ; Stikes, Arterberry, & Logsdon, ) or subscales (Brown, ; Olson, , ), whilst others administered an entire tool, but only reported elements of it (Caris‐Verhallen, Kerkstra, van der Heijden, & Bensing, ; Gilbert, ). The inability to make meaningful comparisons across studies hinders the scientific progression of this body of work and is arguably a further contributing factor to the substantial volume and variability in the literature.…”
Section: Discussionmentioning
confidence: 99%